2019
DOI: 10.3390/su11082259
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dynamic Coupling Relationship between Agricultural Economy and Agro-Ecological Environment in Semi-Arid Areas: A Case Study of Yulin, China

Abstract: The rapid expansion of agricultural areas in semi-arid China over the past decades has aggravated the imbalance of the agroeconomy and agroecological environment. To further understand the coupling relationship between the two, this paper, taking Yulin as a case, develops an integrated index system for evaluation of the agricultural economy and the agroecological environment, and a model of the coupling coordination degree for evaluation of the dynamic coupling relationship between the two. Based on that, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Step 12 Area constraint ∑ n j=1 s j ≤ S, min s j ≤ s j ≤ max s j (13) S is the total area of cultivated and irrigated land; mins j and maxs j are the minimum and maximum planting areas, respectively, of crop j.…”
Section: Metric Formula Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 12 Area constraint ∑ n j=1 s j ≤ S, min s j ≤ s j ≤ max s j (13) S is the total area of cultivated and irrigated land; mins j and maxs j are the minimum and maximum planting areas, respectively, of crop j.…”
Section: Metric Formula Descriptionmentioning
confidence: 99%
“…Rainfed farming is characterized by extensive planting, low yields, and abandonment in drought years. Extensive management and development easily fall into a vicious cycle of exploitation-abandonment-redevelopment-abandonment [13][14][15]. The suitability of the scale of irrigated and rainfed agriculture directly affects the stability of semi-arid Land 2022, 11, 1621 2 of 13 sandy regions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Given the special geographic location and ecological environment of rural areas, rural areas are potential for the development of renewable energy. On the one hand, rural areas with abundant spatial resources are rich in wasteland, rooftops, and other vacant land resources, thus becoming a priority area for the development of solar and wind energy [4]. On the other hand, biomass is mainly distributed in rural areas, indicating an important resource advantage for rural areas [5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve sustainable agricultural development, several scholars have analyzed the impact of agricultural production from the perspectives of global climate and desertification [21][22][23][24], and proposed that it is necessary to adopt water saving measures such as drip irrigation and biological water saving in the development of precision agriculture [25,26]. Research on analysis of the degree to which coupling occurs between two or three systems from the perspective of system coordination has become popular [27][28][29][30][31], with many researchers analyzing and researching agricultural ecosystems and economic systems [32][33][34][35][36][37]. However, few studies have reported on the coupling coordination in agricultural oasis eco-economic systems in arid areas, rendering it imperative that the current situation in terms of the oasis agricultural eco-environment and economic development is analyzed to solve the contradiction between the two, allowing sustainable development of the agricultural eco-environment while increasing the economic benefits.…”
Section: Introductionmentioning
confidence: 99%